Evaluation of Reproducibility of Measurements of Peripapillary Blood Flow with Laser Speckle Flowgraphy in Healthy and POAG Subjects - von Vopelius-Feldt, Alexander; Hamann, Timothy; Mayr, Andreas; Töteberg-Harms, Marc (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Peripapillary blood flow is of diagnostic value in glaucoma.Material and Methods We investigated the reproducibility of peripapillary blood flow measurements in healthy individuals and in open-angle glaucoma (OAG) patients with the Nidek laser speckle flowgraphy (LSFG)-NAVI system. Blood flow was calculated as the mean of vascular area (MV), mean of tissue area (MT), and mean of overall flow (MA). Intra-rater, inter-session, and inter-rater reproducibility were assessed by determining the intraclass correlation coefficient (ICC) and coefficient of variance (COV).Results There were 28 healthy subjects and 16 patients with OAG who participated in this prospective single-center trial. ICC and COV of intra-rater reproducibility were assessed in MV as 0.901; 6.424, MT as 0.909; 4.025, and MA as 0.965; 4.168. Inter-session reproducibility yielded ICC and COV values of MV (0.834; 9.223), MT (0.904; 6.215), MA (0.909; 7.069). Inter-rater reproducibility was computed for MV as 0.78; 9.758, MT as 0.890; 7.210, and MA as 0.888; 6.942. There was a significant difference in MA (p = 0.0184) between the healthy individuals (mean 36.299) and the OAG group (mean 24.944), which was not observed for MV (p = 0.0735) or MT (p = 0.1351).Conclusion High reproducibility of measurements of peripapillary blood flow with the LSFG system was demonstrated in both groups. There is a difference in peripapillary blood flow between healthy controls and OAG patients.
Keywords: glaucoma; perfusion; laser speckle flowgraphy